2016
DOI: 10.1016/j.joca.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of collagen cross-linking on quantitative MRI parameters of articular cartilage

Abstract: Threose treatment induced collagen cross-linking and changes in the properties of articular cartilage, which were detected by T1, T1Gd and T1ρ relaxation time constants. Cross-linking should be considered especially when interpreting the outcome of contrast-enhanced MRI in aging populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…Importantly, this study found significant, inverse correlations between pyridinoline cross-links and both T1 time and T2 time of self-assembling fibrocartilage. These findings corroborate recent work demonstrating a relationship between qMRI metrics and cross-link content in native articular cartilage [42]. It is known that molecular size and rate of molecular motion in a tissue influences the tissue’s T1 and T2 times [43].…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, this study found significant, inverse correlations between pyridinoline cross-links and both T1 time and T2 time of self-assembling fibrocartilage. These findings corroborate recent work demonstrating a relationship between qMRI metrics and cross-link content in native articular cartilage [42]. It is known that molecular size and rate of molecular motion in a tissue influences the tissue’s T1 and T2 times [43].…”
Section: Discussionsupporting
confidence: 89%
“…Human osteochondral plugs (N = 33, d = 8 mm) were extracted from the lateral and medial tibial plateaus and femoral condyles in left and right knee joints of human cadavers (n = 4, mean age = 71.25 ± 5.18 years). [27][28][29] The Research Committee of the Northern Savo Hospital District granted a favorable opinion on collecting the human tissue (Kuopio University Hospital, Kuopio, Finland, Decision numbers: 134/2015 and58/2013).…”
Section: Sample Extraction and Preparationmentioning
confidence: 99%
“…Thickness can be an important factor when choosing the imaging facility particularly when investigating zone-dependent transport properties. For example, even 9.4 T MRI provides relatively low resolutions in out -of-plane orientation (Figure 1) (Rautiainen et al, 2016), which hampers the 3D characterizations, particularly in very thin cartilage of small animals. Therefore, for mice and rat cartilage, the preferred modalities would be either micro-CT (voxel size ~ a few microns) or fluorescent microscopy techniques (planar resolution <1 µm).…”
Section: Tissue Thicknessmentioning
confidence: 99%